Teaching Vocabulary Through Play: The Circle Game In An Indonesian Classroom - Ananda, Tri; Munir, Syahrul; Anggreni, Afrillia (English Language Teaching Methodology, 2025)
Vocabulary acquisition remains a persistent challenge in English as a Foreign Language (EFL) classrooms, particularly in relation to spelling accuracy, word meaning, and contextual usage. Addressing this issue, the present study investigates the effectiveness of the Circle Game as an interactive teaching strategy aimed at improving vocabulary mastery among eighth-grade students at SMP Negeri 1 Sindue Tobata. Employing a quasi-experimental design, 50 students were divided into control and experimental groups. The experimental group engaged in six Circle Game sessions, while the control group received traditional instruction. Data were collected through pre- and post-tests. Results indicated a notable increase in the vocabulary scores of the experimental group, rising from a mean score of 55.36 to 86.8, compared to the control group's improvement from 60.4 to 68.4. A t-test analysis confirmed the statistical significance of the difference between the two groups (t = 7.56 > 2.011). This study highlights the urgency of adopting engaging, student-centered methods in EFL instruction. The findings suggest that game-based strategies like the Circle Game can significantly boost vocabulary learning, motivation, and classroom interaction.